A COMPARISON OF THE HAPPINESS OF PRIMARY SCHOOL STUDENTS IN THE KINGDOM OF BHUTAN AND IN JAPAN - Hayashibara, Shin (PEOPLE: International Journal of Social Sciences, 2019)
Bhutan garnered attention by setting ‘Gross National Happiness’ (GNH) as a national policy to support the foundation of the country. The purpose of this study is to investigate whether primary school students in Bhutan are happy and to identify the characteristics of this happiness. The studies compared the happiness of primary school students in Bhutan and Japan. Participants in the investigation were from primary schools and in the 4th to 6th grades. The participants in the study were 48 students of a private primary school in Bhutan, 47 students of a private elementary school in Japan and 50 students of a public elementary school in Japan. The variance analysis was conducted to compare the degree of happiness by school. As a result, the effect between schools was significant (F (2,142) = 3.99, p < .05). According to multiple comparisons using Tukey b, ‘Bhutan’ was significantly higher than ‘Japan/Public’ (p < .05) in terms of happiness. The tendency of ‘when they are happy?’ shows that the students in Bhutan reported feeling happy in their relationships with people in their daily lives. Likewise, the tendency of ‘what do you want now?’ shows that students in Bhutan want to obtain things in the future, not the present. It was suggested that primary school students in Bhutan were relatively satisfied with what they have presently, and their future dreams and hopes may enhance the present subjective happiness.